2018
DOI: 10.31744/einstein_journal/2018rb4587
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology and multipotent adult progenitor cells in Reparative Medicine: therapeutic perspectives

Abstract: The biology of stem cells is one of the most dynamic and promising fields of the biological sciences, since it is the basis for the development of organisms. Its biological complexity demands efforts from several lines of research aimed mainly at its therapeutic use. Nanotechnology has been emerging as a new field of study, which shows great potential in the treatment of various diseases. This new area of health has been called “Nanomedicine” or “Bionanotechnology”, which can be applied in Medicine by transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Schwann cells, fibroblasts and macrophages also play important roles in regulating the regeneration microenvironment and improving the regeneration effect through a variety of manual interventions ( Qian et al, 2019 ). Therefore, in peripheral nerves, stem/progenitor cells present potentials in the treatment, cure, and repair of damaged tissues secondary to injury and inflammation ( Mazzeo and Santos, 2018 ). In such a context of inflammation and nerve injury, the sciatic nerve is especially exposed because of its very special anatomical feature: it is the largest peripheral nerve in the human body, but also the most exposed to forces of torsion, traction and pressure during daily activities ( Sladjana et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells, fibroblasts and macrophages also play important roles in regulating the regeneration microenvironment and improving the regeneration effect through a variety of manual interventions ( Qian et al, 2019 ). Therefore, in peripheral nerves, stem/progenitor cells present potentials in the treatment, cure, and repair of damaged tissues secondary to injury and inflammation ( Mazzeo and Santos, 2018 ). In such a context of inflammation and nerve injury, the sciatic nerve is especially exposed because of its very special anatomical feature: it is the largest peripheral nerve in the human body, but also the most exposed to forces of torsion, traction and pressure during daily activities ( Sladjana et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] According to information contained in a 2018 article on nanotechnology-associated progenitor cell therapy, there was an increase from a previous 1%, to 100% of myocyte regeneration, emphasizing the benefits brought by the use of nanoparticles. 5 A study with unique features developed an ultrasoundactivated oxygen-generating nanosystem that can release O2 specifically into the infarcted cardiomyocyte, relieving hypoxemia and protecting the surrounding tissue after the AMI episode, as well as reducing oxidative stress. 28 When it comes to HF, the idea of using cardiovascular tissues by engineering process with nanomaterials has been widely discussed.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the new allotropic species of carbon known today as fullerenes, and finally the invention of tunneling and atomic force microscopes, have enabled the visualization and manipulation of structures at an atomic level, boosting pure and applied research with nanomaterials. 3,4 The advancement of this nanometric technology started with physicist Richard Feynman 5 and since then has opened a series of opportunities in different scientific fields. 6,7 In this sense, studies with nanoparticles directed to CVDs have shown increasingly satisfactory results.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous advancement in nanotechnology, combining stem cells and exosomes with nanotechnology makes treatment more precise and effective. Nanotechnology can allow stem cells to be targeted to specific locations and can also help stem cells in applying their therapeutic potential to treat, heal, and repair damaged tissues in an effective and safe manner 210,211 . Nanotechnology can solve the abnormal proliferation and differentiation of stem cells during the treatment process, 212 improves the possibility of reducing the limitations of stem cells in the treatment of cell regeneration in injured or degenerated organs, enhances tissue repair, and assists in cellular reconstruction.…”
Section: Novel Nanoformulations Loaded With Stem Cells and Exosomesmentioning
confidence: 99%